The dynamic equilibrium between the protective and toxic effects of matrine in the development of liver injury: a systematic review and meta-analysis - Feng, Weiyi; Kao, Te-chan; Jiang, Jiajie; Zeng, Xinyu; Chen, Shuang; Zeng, Jinhao; Chen, Yu; Ma, Xiao (Frontiers in Pharmacology, 2024)
Background: Matrine, an alkaloid derived from the dried roots of Sophora flavescens Aiton, has been utilized for the treatment of liver diseases, but its potential hepatotoxicity raises concerns.However, the precise condition and mechanism of action of matrine on the liver remain inconclusive.Therefore, the objective of this systematic review and meta-analysis is to comprehensively evaluate both the hepatoprotective and hepatotoxic effects of matrine and provide therapeutic guidance based on the findings.The meta-analysis systematically searched relevant preclinical literature up to May 2023 from eight databases, including PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), WanFang Med Online, China Science and Technology Journal Database, and China Biomedical Literature Service System. The CAMARADES system assessed the quality and bias of the evidence. Statistical analysis was conducted using STATA, which included the use of 3D maps and radar charts to display the effects of matrine dosage and frequency on hepatoprotection and hepatotoxicity.Results: After a thorough screening, 24 studies involving 657 rodents were selected for inclusion.The results demonstrate that matrine has bidirectional effects on ALT and AST levels, and it also regulates SOD, MDA, serum TG, serum TC, IL-6, TNF-α, and CAT levels. Based on our comprehensive three-dimensional analysis, the optimal bidirectional effective dosage of matrine ranges from 10 to 69.1 mg/kg. However, at a dose of 20-30 mg/kg/d for 0.02-0.86 weeks, it demonstrated high liver protection and low toxicity. The molecular docking analysis revealed the interaction between MT and SERCA as well as SREBP-SCAP complexes. Matrine could alter Ca 2+ homeostasis in liver injury via multiple pathways, including the SREBP1c/SCAP, Notch/RBP-J/HES1, IκK/NF-κB, and Cul3/Rbx1/Keap1/Nrf2.Matrine has bidirectional effects on the liver at doses ranging from 10 to 69.1 mg/kg by influencing Ca 2+ homeostasis in the cytoplasm, endoplasmic reticulum, Golgi apparatus, and mitochondria.